Multimodality Management of Recurrent Skull Base Chordomas: Factors Impacting Tumor Control and Disease-Specific Survival. Issue 2 (10th October 2017) - Raza, Shaan M; Bell, Diana; Freeman, Jacob L; Grosshans, David R; Fuller, Gregory N; DeMonte, Franco
Abstract: BACKGROUND: Limited data exist to guide the management of recurrent chordomas arising in the skull base. OBJECTIVE: To determine factors affecting tumor control rates and disease-specific survival (DSS) in recurrent disease. METHODS: A retrospective review was performed of 29 patients with 55 recurrences treated at our institution. Tumor and treatment factors were assessed for impact on freedom from progression (FFP; primary outcome) and DSS (secondary outcome). RESULTS: Postradiotherapy disease failure was much more difficult to manage vs progression after surgery alone (15.9 vs 41.4 mo, P = .094). Distant metastases and, specifically, leptomeningeal disease at presentation were associated with poorer DSS and FFP ( P < .05). For local progression after surgery alone, repeat resection ( P < .05) improved median FFP. With postradiotherapy local failure, repeat resection did not confer any benefit (13.5 vs 17.6 mo, P > .05), while a trend towards improved FFP was seen with stereotactic radiosurgery (28.3 vs 16.2 mo, P = .233). For distant metastases, site-directed therapy (surgery or radiation) allowed for site control ( P < .05) but did not affect FFP or DSS. Presentation with early progression <6 mo from previous treatment portended significantly worse DSS (19.3 vs 77.6 mo, P < .05). CONCLUSION: There is a need for treatment of recurrent disease to be tailored to the pattern of tumor recurrence and previously received treatments. Postradiotherapy progression poses particular challenges given the apparent limited role of repeat resection alone. Stereotactic radiosurgery may have a role in this setting. While patients with systemic metastases appear to respond well to site-directed therapy, those with leptomeningeal disease have a dismal prognosis.